Do Rural Land Markets Increase Inequality? Evidence from a Chinese Province - Zhang, Qian Forrest (Institutional Knowledge at Singapore Management University, 2005)
Using a 2001 provincial survey, we find that disparities in land-rights distribution have greatly increased in rural China, and the growth of land markets is directly responsible for that. The land markets tend to concentrate land in those who can more efficiently use it. This translates disparities in land-rights distribution to magnified inequality in farm income. However, such widening disparities caused by land markets have compensatory effects on overall rural inequality, as land markets tend to bring up families who would fall at the bottom of income distribution in the absence of such markets. Expansion of markets, in this case, widens the access to market opportunities and help to reduce inequality in an economy that is undergoing both fast development and a transition to market.